Asymptomatic Giant Thoracic Ganglioneuroma: A Rare Case Report and Literature Review - Samara, Qais; Arabyat, Abdallah; Hamouri, Shadi; Awad, Mai (Journal of Neonatal Surgery, 2025)
Background: Ganglioneuroma (GN) is a rare, benign neuroblastic tumor arising from neural crest cells along the sympathetic chain. It is well-circumscribed, slow-growing, and commonly occurs in the posterior mediastinum (41%), retroperitoneum, adrenal gland, and neck. Despite its benign nature, GN can grow significantly without symptoms and is often detected incidentally. Case Description: We report a 22-year-old female with an asymptomatic thoracic ganglioneuroma, incidentally identified during a pre-employment medical check-up. Thoracic MRI revealed a well-defined posterior mediastinal mass (11.7 × 10.2 × 14 cm) occupying the left hemithorax. The tumour was successfully resected via a posterolateral thoracotomy, and histopathology confirmed benign mature ganglioneuroma. Conclusions: Thoracic ganglioneuromas are rare and often asymptomatic, making early detection challenging. Imaging plays a crucial role in diagnosis, and surgical excision remains the preferred treatment for large tumours to prevent complications.